Diethylenetriamine tethered mesoporous silica for the sequestration of uranium from aqueous solution and seawater. Issue 4 (August 2020) - Amesh, P.; Venkatesan, K.A.; Suneesh, A.S.; Samanta, Nibedita
Graphical abstract: Highlights: Preparation of mesoporous silica anchored with diethelentriamine ligand. Characterization of the product by BJH, FT-IR, Small angle XRD, TG-DTA and SEM-EDX. Solid phase extraction of uranium from aqueous phase and seawater. Highest capacity of uranium from aqueous solutions and seawater (1067 and 680 mg.g −1 ). Adsorbent exhibited excellent selectivity and regeneration properties. Abstract: Mesoporous silica (MCM-41) with large surface area and porosity has been synthesized and tethered covalently with the uranium (VI) specific ligand, namely diethylenetriamine (DETA) on MCM-41. The adsorbent, abbreviated as MCM-DETA, was characterized by BET surface area, BJH pore size and particle size distribution, thermogravimetry, SEM-EDX analysis, and FT-IR spectroscopy, and studied for the adsorption of uranium from aqueous solution. The parameters evaluated were the effect of pH of the aqueous phase, duration of equilibration, concentration of uranium in the aqueous phase, and the effect of interfering ions on the adsorption of uranium (VI) on MCM-DETA. The adsorption behavior of uranium from seawater (U(VI) = 10 mg.L −1 ) was studied by batch equilibration method. The results revealed that MCM-DETA showed rapid adsorption kinetics ( k 2  = 2.85 × 10 -3 mol.L −1 . min −1 ), extremely large Langmuir adsorption capacity (1067 mg.g −1 ), good selectivity over other interfering ions, and efficient adsorption of uranium from seawater (680 mg.g −1 ) spiked with uranium, indicating that MCM-DETA a promising candidate for the adsorption of uranium from aqueous solution and seawater.